2023
DOI: 10.3390/pharmaceutics15020712
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Mechanisms of Quercetin in Liver Cancer: Recent Trends and Advancements

Abstract: Due to rising incidence rates of liver cancer and worries about the toxicity of current chemotherapeutic medicines, the hunt for further alternative methods to treat this malignancy has escalated. Compared to chemotherapy, quercetin, a flavonoid, is relatively less harmful to normal cells and is regarded as an excellent free-radical scavenger. Apoptotic cell death of cancer cells caused by quercetin has been demonstrated by many prior studies. It is present in many fruits, vegetables, and herbs. Quercetin targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 99 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…All of these compounds show antitumor properties. Quercetin and kaempferol induced cell cycle arrest and apoptotic cell death in liver cancer cells, and kaempferol had no effect on normal cells [ 55 , 56 ]. Pinocembrin suppressed proliferation and increased apoptosis in lung cancer cells in vitro, and galangin has the same effect in ovarian cancer cells [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of these compounds show antitumor properties. Quercetin and kaempferol induced cell cycle arrest and apoptotic cell death in liver cancer cells, and kaempferol had no effect on normal cells [ 55 , 56 ]. Pinocembrin suppressed proliferation and increased apoptosis in lung cancer cells in vitro, and galangin has the same effect in ovarian cancer cells [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The binding rate of plasma protein of quercetin and its derivatives ranged from 85.36 to 99.82. [95] The ADME properties predicted by the ACD/I-Lab platform indicated that quercetin and 3'-methyl ether quercetin presented a maximum passive absorption of 100 %, whereas all other quercetin derivatives had an absorption of less than 15 %. [96] The intestine and liver are the main sites of quercetin metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…[100] As a main metabolite of quercetin, quercetin-3-O-β-D-glucuronide can be transported to target tissues via plasma to exert the corresponding biological activity. [95] The half-life of quercetin metabolites is range from 11 to 28 hours. Absorption of quercetin is highly individualized, which may be caused by variations in metabolic enzymes and transporters in the intestine and liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations